THE CONCEPT OF ABBREVIATION AND ITS LINGUISTIC ESSENCE - Shermatov Akram Abdukhakimovich; Tolibova Durdona Mamajonovna; Quziboyeva Sarvinoz Xayrullo qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Abbreviation is one of the most productive and widely used word‑formation processes in modern languages. It allows speakers to shorten long words and expressions and facilitates faster and more effective communication. The aim of this article is to analyze the linguistic essence of abbreviation and identify its main structural types in modern English and Uzbek languages. The research is based on descriptive, comparative and functional linguistic methods. The results show that abbreviations such as initialisms, acronyms, clippings and blends play an important role in modern communication and reflect social, technological and cultural development. The study also highlights similarities and differences between abbreviation processes in English and Uzbek.